62 Innovating and improving the teaching programme for medical students at royal surrey county hospital. (3rd November 2019) - Lu, Mengfei; Cole, Andrew; Levinson, Gavriella; Bamania, Prashant
Abstract : Introduction: The transition from medical school to the NHS Foundation programme can be challenging. This project aimed to use these standards to improve the service provision and quality of medical student teaching at RSCH to develop a teaching programme tailored to support final year medical students as they prepare to become the new generation of Doctors. Methods: There were four elements of the teaching program: Mock OSCE: Practical assessment of clinical skills with individualised feedback. Bedside teaching: FY1 led teaching on inpatients at RSCH. Lecture based teaching: Weekly lectures delivered by FY1's covering all aspects of the medical curriculum. Mentorship programme: Final year students assigned to FY1's for career advice. Results: Mock OSCEs 100% of students found it useful and well organised. Recruitment of real patients was largely unsuccessful thus necessitating the use of professional actors. Bedside teaching 100% of FY1's enjoyed this form of teaching and felt a list of students was provided in a timely manner. The teaching was not timetabled, and it was noted there was difficulty in arranging the teaching. 85% of FY1's felt this was due to conflicting schedules. Lecture based teaching 100% of participants enjoyed this form of teaching. Importantly a senior doctor observed none of the lectures. FY1's received feedback directly from medical students. Mentorship program: This program was unsuccessful due to 1) limited FY1 and medical student time 2) unclear distinction between bedside teaching and mentoring program. Conclusion: Both FY1's and students benefit from medical education Observation of lecture–based teaching from a senior doctor with constructive feedback is needed Mock OSCE could be expanded to cover more topics. Consultant–led patient recruitment will improve Mock OSCE Mentoring and bedside teaching should be combined with clinical and social support provided by the same F1